Grounded Identities, Transient Lives: The Emergence of International Student Voices in an Era of Cosmopolitan Learning - Gargano, Terra (Journal of International Students, 2012)
This paper is an exploration of the identity negotiations of two international undergraduate students at a public research university in the United States. Studying abroad constitutes a culturally contested space for educational sojourners, with ruptures that require constant sense-making and negotiations of identities as students attempt to combine the foreign and the familiar. Situational contexts, interpersonal interactions, and the imagination all determine what students learn and how that learning occurs. However, the influence of cosmopolitan learning on the identity negotiations of students is little understood. The experiences of foreign students in many ways challenge the traditional understanding of an international education and the categorization of a traditional international student. Focusing almost exclusively on nationality as an organizing agent and bereft of significant and robust concepts that bring into view the content of international student sense-making, international education discourses neglect to explore the complexity and meanings students ascribe to educational sojourns.